ظاهرة السلم في السيرة النبوية: Peace Phenomenon in Prophetic Seerah - Dr. Abdul Wahaab Jan Alazhari (MEI, 2023)
The Holy Prophet Muhammad (PBUH) came to the world as a universal and eternal prophet with a status of "Mercy for the worlds". It was an essential requirement of this status of universal mercy for the world to make this world the cradle of peace and security. For this, where the spirit of peace and security was instilled in him, the message that he conveyed to the people of Allah Almighty was also a message of complete peace and security in terms of its meaning and teachings. Since Prophet Muhammad (Peace and blessings be upon him) came as a mercy to the whole world without any distinction of profession, ideology, race or region, He promoted peace and security in the society together with protection of life, property and honor of every human being by taking such numerous far-reaching security measures that have at least made the Arabian Peninsula at that time a heaven of peace. His attitude towards the polytheists of Makkah and the people of the Book (Ahl al Kitab) was also exemplary. At the time of the Prophet's revelation, the world was a hotbed of strife and disorder as no one's life was safe, neither wealth, nor honor of any one was safe and even no way was safe but the world welcomed a great revolution after following the prophetic teachings. The present time is also facing a very multifaceted difficult situation and if the teachings and instructions of the Holy Prophet Muhammad (PBUH) regarding peace and security are followed, the global village can become the cradle of peace and security. A descriptive research method has been adopted in this article.